Lobbying activities of multinational firms - Andreas Polk (University of Zurich, Socioeconomic Institute, 2002)
This paper investigates if multinationals in.uence the political process through lobbying more effectively than national firms. First, I introduce a model which contrasts a multinational's incentives for lobbying with those of a national firm. Then the effect of lobbying on the political decision is analyzed. I conclude that multinationals have smaller incentives to lobby because they have smaller stakes in national markets. But the effectiveness of lobbying by multinationals might be higher if the government cares much about production in the home country. The resulting regulation depends on the relative strength of these effects.
Keywords: D72; F23; L51; 330; multinational enterprizes; regulation; policy formation; lobbying; interest groups; foreign direct investment; Multinationales Unternehmen; Interessenpolitik; Direktinvestition; Theorie; Policy-Ansatz